Two new species of scalpelliform barnacles (Cirripedia: Thoracica) from the Plio-Pleistocene of Cotentin, northwest France - Carriol, René-Pierre (Zootaxa, 2013)
Two new species of pedunculate cirripede are described from the Plio-Pleistocene of Cotentin, northwest France. Scalpel-lum carentanensis sp. nov. is only the third species of this genus to be recorded from Pliocene strata in Europe. It is char-acterised by a triangular tergum with an apico-basal fold, without an outward extension, the inner surface of which has the raised part marked by wide growth lines, cut by a groove; the scutum has a ridge between the umbo and the tergo-lateral angle, lacks an apico-basal ridge, and possesses a line formed by the convergence of the growth zones; the length of the upper lateral exceeds its width by about 1.25 times, the umbo being situated at one-fifth the length of the plate from the apex. Arcoscalpellum concavitectum sp. nov. is the second species of this genus on record from the Pliocene of Europe. It possesses a carina with a concave tectum bordered on each side by a smooth rounded rib; the tergum has an apico-basal line formed by the convergence of growth zones; and the upper lateral has the basi-scutal angle more widely truncated than the basi-tergal angle.